Classifying trunk strength impairment according to the activity limitation caused in wheelchair rugby performance - Altmann, V. C.; Groen, B. E.; Hart, A. L.; Vanlandewijck, Y. C.; Keijsers, N. L. W. (Scandinavian Journal of Medicine & Science in Sports, 2018)
International Federations in Paralympic sport should develop evidence based classification, based on the relative strength of association between impairment and activities that determine sport specific performance. The purpose of the current study was to assess the relationship between trunk strength impairment and three activities that determine performance in Wheelchair Rugby, and to determine whether this relationship supports the concept of "natural classes". Trunk muscle strength and three determinants of performance were assessed in 27 athletes The correlations between lateral trunk muscle strength and the determinant tilting the chair, and between forward trunk muscle strength and the determinants 1 m acceleration and sprint momentum were calculated. To group athletes based on impairment, K-means cluster analysis was used to group athletes according to how much trunk muscle strength affected the activities. There were significant, moderate to strong correlations between left-right strength and chair tilting (r = .50), between forward strength and 1 m acceleration (r = .59) and between forward strength and sprint momentum (r = .79). Cluster analysis indicated at least one cut-point in performance with a decrease in impairment in all three wheelchair activities, supporting the concept of "natural classes".